Early-Time Non-Equilibrium Pitch Angle Diffusion of Electrons by Whistler-Mode Hiss in a Plasmaspheric Plume Associated with BARREL Precipitation - Millan, R. M.; Ripoll, J.-F.; Santolík, O.; Kurth, W. S. (Frontiers in Astronomy and Space Sciences, 2021)
In August 2015, the Balloon Array for Radiation belt Relativistic Electron Losses (BARREL) observed precipitation of energetic (~10-150 keV) electrons magnetically conjugate to a region of dense cold plasma as measured by the twin Van Allen Probes spacecraft. The two spacecraft passed through the high density region during multiple orbits, showing that the structure was spatial and relatively stable over many hours. The region, identified as a plasmaspheric plume, was filled with intense hiss-like plasma waves. We use a quasi-linear diffusion model to investigate plume whistler-mode hiss waves as the cause of precipitation observed by BARREL. The model input parameters are based on the observed wave, plasma and energetic particle properties obtained from Van Allen Probes. Diffusion coefficients are found to be largest in the same energy range as the precipitation observed by BARREL, indicating that the plume hiss waves were responsible for the precipitation. The event-driven pitch angle diffusion simulation is also used to investigate the evolution of the electron phase space density for different energies and assumed initial pitch angle distributions. The results show a complex temporal evolution of the phase space density composed of periods of growth and loss. The earliest dynamics, within the ~5 first minutes, can be controlled by a growth of the PSD near the loss cone (by a factor up to ~2, depending on the conditions, pitch angle, and energy), favored by the absence of a gradient at the loss cone and by the gradients of the initial pitch angle distribution. Global loss by 1-3 orders of magnitude (depending on the energy) are computed within the ~100 mins of wave-particle interaction. The prevalence of plasmaspheric plumes and detached plasma regions suggests plasmaspheric hiss could be an important driver of electron loss even at high L-value (L~6), outside of the main plasmasphere.